Silver nanoparticles loaded with pomegranate peel extract and hyaluronic acid mediate recovery of cutaneous wounds infected with Candida albicans - El-Hamid, Marwa I. Abd; Ibrahim, Doaa; Abdelfattah-Hassan, Ahmed; Mohammed, Osama B.; Pet, Ioan; Khalil, Samah S.; El-Badry, Sara M.; Metwally, Aya Sh.; Azouz, Asmaa A.; Elnegiry, Ahmed A.; Elnahriry, Shimaa S.; Ahmadi, Mirela; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Smart innovative nanocomposites based on active ingredients and metallic nanoparticles with effective wound healing and antifungal properties are efficient in overcoming the limitations of traditional therapeutic products. Open wounds provide an ideal niche for colonization by Candida albicans (C. albicans) which poses substantial global health issues owing to delayed wound healing and disordered healing mechanisms. Therefore, proficient innovative therapies that control C. albicans infection and promote wound healing are of imperative importance for the management of wounds and prevention of infection and possible complications. This study aims to design a novel nanocarrier platform based on a hydrogel loaded with silver nanoparticles (AgNPs) and doped with pomegranate peel extract (PPE) and hyaluronic acid (HA), offering an unprecedented opportunity to achieve skin repair and manage C. albicans colonization with an efficient wound healing process. Sprague-Dawley rats (n=100) were assigned to 5 groups and infected with C. albicans and distributed as follows: control positive (untreated) and four cutaneous wound-healing model groups treated topically with commercial cream and PPE-HA-AgNPs at full, 50%, and 25% concentrations for 15 days, respectively. Our findings revealed that the severity of clinical signs, C. albicans burden, and the expression of biofilm-related genes ALS1, HYR1, and PLB1 were diminished following treatment with PPE-HA-AgNPsIII. Notably, the formulated nanocomposite was very effective in extending the release of PPE-HA-AgNPs in infected wounds with retention percentages of 65.4% for PPE-HA-AgNPsIII. Topical administration of PPE-HA-AgNPsIII successfully alleviated the extensive inflammatory response and healed wounded skin via downregulation of tumor necrosis factor-alpha (TNF-α), interleukin-6 and IL-1 beta, and nitric oxide synthase (NOS) levels as shown by enzyme-linked immunosorbent (ELISA) and reverse transcription-quantitative polymerase chain reaction (RT-qPCR) assays. Interestingly, PPE-HA-AgNPsIII modulated angiogenic and wound healing markers as evidenced by the downregulation of MMP-9 and the upregulation of angiopoietin-1 (Ang-1), vascular endothelial growth factor (VEGF) (up to 10 days post-treatment), transforming growth factor-beta 1 (TGF-β1), bFGF, EGF, Ki-67, and collagen I and III with efficient wound closure capability. This was evidenced by the lessening of histopathological severity, which accelerated the healing of the infected skin wounds post-treatment with PPE-HA-AgNPs. Overall, our formulated PPE-HA-AgNPs provide an effective innovative therapeutic strategy for the treatment of cutaneous wounds infected with C. albicans with maximized wound healing efficacy, indicating their potential in clinical practice.